Heat treatment method for directionally solidifying high-carbon nickel-based composite material and high-carbon nickel-based composite material

Through the combination of solid solution treatment and aging treatment, the γ′ phase and carbide microstructure in the directionally solidified high-carbon nickel-based composite material is regulated, which solves the problem of coarse and unevenness of the γ′ phase, and significantly improves the mechanical properties and creep life of the alloy.

CN119553199APending Publication Date: 2025-03-04NORTHWESTERN POLYTECHNICAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411737206.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

The γ′ phase in the directionally solidified high-carbon nickel-based composite material is coarse and uneven, which affects the alloy performance. The existing heat treatment process cannot effectively regulate the microstructure of the γ′ phase and carbides, resulting in poor strengthening effect.

Method used

By using a combination of solution treatment and aging treatment, the size, volume fraction and carbide morphology of the γ′ phase are controlled by controlling the solution treatment temperature (1260-1320°C) and time (3-5h), as well as the aging treatment temperature (800-1000°C) and time (2-10h), the size, volume fraction and carbide morphology are controlled, so that the γ′ phase is refined, the cubicity is high, the volume fraction is appropriate, and the carbide is controlled to transform into fine particles that are easy to pin.

Benefits of technology

The refinement and uniform distribution of the γ′ phase is achieved, the tensile strength, yield strength and creep life of the alloy are improved, and the mechanical properties of the material are enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119553199A_ABST
    Figure CN119553199A_ABST
Patent Text Reader

Abstract

The invention provides a heat treatment method for a directionally solidified high-carbon nickel-based composite material, and belongs to the technical field of heat treatment of nickel-based composite materials. The high-carbon nickel-based composite material is a carbide and gamma'phase complex-phase reinforced high-temperature structural material, a coarse primary gamma 'phase in a structure is dissolved by controlling parameters of solution treatment, conditions are created for uniform precipitation of a secondary gamma' phase, meanwhile, the carbide at a grain boundary is converted, and the M6C carbide is precipitated at the grain boundary; the morphology and size of a secondary gamma'phase and carbide are regulated and controlled through aging treatment, so that the gamma 'phase has high interface stability, the strengthening effect of the gamma' phase is improved, and meanwhile, M23C6 carbide separated out in the aging treatment process is distributed in a fine and discrete point shape; and secondary gamma'phase and carbide separated out after heat treatment can hinder dislocation motion, inhibit grain boundary slippage and greatly improve the mechanical property of the nickel-based composite material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of heat treatment of nickel-based composite materials, and in particular to a heat treatment method for a directionally solidified high-carbon nickel-based composite material and the high-carbon nickel-based composite material. Background Art

[0002] Nickel-based high-temperature alloys have good structural stability and creep resistance at high temperatures and are widely used in aerospace engine turbine blades. As the service conditions of aerospace equipment become more and more demanding, the performance requirements for high-temperature alloys are also constantly increasing. At present, aerospace engine design units have proposed aerospace engine design concepts with high economy, high temperature bearing capacity and high reliability. By adding carbon elements to high-temperature alloys to form eutectic composite materials reinforced by carbide fibers and γ′ phases, the material's temperature bearing capacity, high temperature strength, corrosion resistance and mechanical processing properties can be improved, and casting / solidification defects can be reduced. However, studies have found that the γ′ phase in the cast structure of directionally solidified high-carbon nickel-based composites is coarse and uneven. This coarse and irregular γ′ phase is generally considered to be detrimental to the performance of the alloy.

[0003] Heat treatment process is an important means to adjust the microstructure of alloys and improve the mechanical properties of alloys. Studies have shown that the γ′ phase in the cast alloy structure of nickel-based high-temperature alloys can be regulated by solution treatment (1150-1320°C), high-temperature aging treatment (1050-1150°C) and low-temperature aging treatment (750-950°C). When the γ′ phase is cubic, the size is 0.3-0.5μm, and the volume fraction is 65%, the strengthening effect of the alloy is the best. However, after heat treatment of the directionally solidified high-carbon nickel-based composite material using the above heat treatment process, the γ′ phase is still relatively coarse, and the heat treatment will induce the undesirable transformation of carbides, and the best strengthening effect cannot be obtained. Summary of the invention

[0004] The purpose of the present invention is to provide a heat treatment method for a directionally solidified high-carbon nickel-based composite material and a high-carbon nickel-based composite material. The heat treatment method provided by the present invention can refine the size of the γ′ phase in the directionally solidified high-carbon nickel-based composite material, increase the cubic degree, and have an appropriate volume fraction, and at the same time control the transformation of carbides during the heat treatment process to form fine granular carbides that are easy to pin the grain boundary, so as to improve the tensile strength, yield strength and creep life of the alloy.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The invention provides a heat treatment method for a directionally solidified high-carbon nickel-based composite material, comprising: subjecting the directionally solidified high-carbon nickel-based composite material to a solution treatment and an aging treatment in sequence; the temperature of the solution treatment is 1260-1320°C, and the holding time is 3-5 hours; the temperature of the aging treatment is 800-1000°C, and the holding time is 2-10 hours.

[0007] Preferably, the temperature of the solution treatment is 1280-1310° C., and the holding time is 3.5-4.5 h.

[0008] Preferably, the aging treatment is performed once or twice.

[0009] Preferably, when the aging treatment is performed once, the aging treatment is low-temperature aging; the temperature of the low-temperature aging is 800-900° C., and the time is 2-10 h.

[0010] Preferably, when the aging treatment is performed twice, the aging treatment is high temperature aging and low temperature aging performed sequentially.

[0011] Preferably, the temperature of the high-temperature aging is higher than 900° C. and not higher than 1000° C., and the time is 2 to 4 hours; the temperature of the low-temperature aging is 800 to 900° C., and the time is 2 to 6 hours.

[0012] Preferably, the composition of the directionally solidified high carbon nickel-based composite material is as follows by mass percentage: 9.5-11.0% Co, 5.5-6.5% Al, 3.0-3.5% Nb, 8.0-9.0% Cr, 1.6-2.5% Mo, 7.2-7.9% W, 0.4-0.46% C, 0.4-0.55% V, and the balance Ni.

[0013] Preferably, the directionally solidified high carbon nickel-based composite material is prepared by liquid metal cooling technology.

[0014] The present invention also provides a high-carbon nickel-based composite material obtained by the heat treatment method of the above technical solution, wherein the microstructure of the high-carbon nickel-based composite material includes a γ phase, a γ′ phase and carbides, wherein the γ′ phase is cubic, the size of the γ′ phase is 306 to 445 nm, and the volume fraction of the γ′ phase is 63.4 to 67.7%; the carbides include MC, M6C and M 23 C6 carbide.

[0015] Preferably, the MC carbide is fibrous; the size of the M6C carbide is less than 12 μm, and the area fraction is not higher than 1.5%; 23 The size of C6 carbides is less than 500 nm.

[0016] The present invention provides a heat treatment method for a directionally solidified high-carbon nickel-based composite material, comprising: subjecting the directionally solidified high-carbon nickel-based composite material to a solution treatment and an aging treatment in sequence; the temperature of the solution treatment is 1260-1320°C, and the holding time is 3-5 hours; the temperature of the aging treatment is 800-1000°C, and the holding time is 2-10 hours. The present invention dissolves the coarse primary γ′ phase through the solution treatment, thereby creating conditions for the uniform precipitation of the secondary γ′ phase; controls the transformation of carbides at the grain boundaries during the solution treatment, and uniformly precipitates M6C carbides at the grain boundaries; further regulates the secondary γ′ phase and carbides through the aging treatment, and controls the cubicity, size, and volume fraction of the γ′ phase by controlling the temperature and time of the aging treatment, so that the γ′ phase is uniformly distributed with high density, and the cubic γ′ phase has high interface stability, reduces interface energy, and can uniformly disperse stress; at the same time, controls the precipitation of M6C carbides during the aging treatment. 23 C6 carbide, making it distributed in small, discrete points; the secondary γ′ phase and carbide precipitated after heat treatment have the effect of pinning dislocations, which can hinder dislocation movement, inhibit grain boundary sliding, and greatly improve the tensile properties and creep properties of nickel-based composite materials. The results of the embodiment show that after the directionally solidified high-carbon nickel-based composite material is treated by the heat treatment method provided by the present invention, the γ′ phase in the organization is cubic, with a size of 306 to 445nm and a volume fraction of 63.4 to 67.7%; MC does not change much and is fibrous; the size of M6C carbide is less than 12μm, and the area fraction is 0.67% to 1.46%; M 23 The size of C6 carbide is less than 500nm and is granular; the obtained high-carbon nickel-based composite material has a tensile strength of 923.33MPa at 900℃, a yield strength of 856.96MPa, and a creep life of 222.97h at 1000℃ and 180MPa. BRIEF DESCRIPTION OF THE DRAWINGS

[0017] Figure 1 is a flow chart of a heat treatment method in an embodiment of the present invention;

[0018] Figure 2 The as-cast microstructure morphology of the directionally solidified high-carbon nickel-based composite material prepared in Comparative Example 1, wherein (a) is the microstructure morphology of MC carbide, and (b) is the microstructure morphology of γ-γ′ phase;

[0019] Figure 3 The microstructures of the high carbon nickel-based composite materials after solution treatment in Examples 1 to 4 are shown in Figures 1 to 4, wherein (a) and (e) are at 1260°C, (b) and (f) are at 1280°C, (c) and (g) are at 1300°C, and (d) and (h) are at 1320°C;

[0020] Figure 4 This is a microstructure morphology of M6C precipitated from the high carbon nickel-based composite material after solution treatment in Example 4;

[0021] Figure 5 The microstructures of the high carbon nickel-based composite materials obtained by heat treatment in Examples 1 and 5 to 8 are shown in Figures 1 and 8, wherein (a) is 1300°C / 4h+870°C / 2h; (b) is 1300°C / 4h+870°C / 4h; (c) is 1300°C / 4h+870°C / 6h; (d) is 1300°C / 4h+870°C / 8h; (e) is 1300°C / 4h+870°C / 10h;

[0022] Figure 6 The microstructure of the high-carbon nickel-based composite material obtained by heat treatment in Example 8, wherein (a) is M 23 C6 microstructure morphology, (b) is the microstructure morphology of MC carbide;

[0023] Figure 7 The microstructures of the high-carbon nickel-based composite materials obtained by heat treatment in Examples 9 to 10, wherein (a) is 950°C / 2h+870°C / 4h, and (b) is 950°C / 4h+870°C / 4h;

[0024] Figure 8 The microstructure morphology of the high carbon nickel-based composite material obtained by heat treatment in Comparative Examples 2 to 3, wherein (a) is 1050°C / 2h+870°C / 4h, and (b) is 1050°C / 4h+870°C / 4h;

[0025] Fig. 9 It is a comparison chart of the tensile curves of the high-carbon nickel-based composite materials obtained in Comparative Example 1, Example 1 and Example 10. DETAILED DESCRIPTION

[0026] All raw materials of the present invention have no particular limitation on their sources and can be purchased from the market or prepared according to conventional methods known to those skilled in the art.

[0027] There is no particular limitation on the purity of all raw materials in the present invention. The present invention preferably uses high-purity or conventional purity in the field of nickel-based alloys.

[0028] The invention provides a heat treatment method for a directionally solidified high-carbon nickel-based composite material, comprising: subjecting the directionally solidified high-carbon nickel-based composite material to a solution treatment and an aging treatment in sequence; the temperature of the solution treatment is 1260-1320°C, and the holding time is 3-5 hours; the temperature of the aging treatment is 800-1000°C, and the holding time is 2-10 hours.

[0029] The invention sequentially performs solution treatment and aging treatment on the directionally solidified high-carbon nickel-based composite material.

[0030] In the present invention, the composition of the directionally solidified high-carbon nickel-based composite material is preferably 9.5-11.0% Co, 5.5-6.5% Al, 3.0-3.5% Nb, 8.0-9.0% Cr, 1.6-2.5% Mo, 7.2-7.9% W, 0.4-0.46% C, 0.4-0.55% V, and the balance Ni. The present invention limits the composition and amount of the alloy to the above range, which is conducive to improving the strength and toughness of the alloy. As an embodiment of the present invention, the composition of the directionally solidified high carbon nickel-based composite material can be 9.8-10.7% Co, 5.7-6.3% Al, 3.1-3.4% Nb, 8.1-8.9% Cr, 1.8-2.3% Mo, 7.3-7.8% W, 0.41-0.45% C, 0.41-0.50% V, and the balance Ni; it can also be 10.0-10.5% Co, 5.8-6.2% Al, 3.2-3.3% Nb, 8.2-8.8% Cr, 1.9-2.2% Mo, 7.4-7.7% W, 0.43-0.44% C, 0.43-0.48% V, and the balance Ni.

[0031] In the present invention, the directionally solidified high-carbon nickel-based composite material is preferably prepared by liquid metal cooling technology. The present invention has no special requirements on the specific parameters of the liquid metal cooling technology, as long as the directionally solidified high-carbon nickel-based composite material can be obtained. As an embodiment of the present invention, the liquid metal cooling technology can use Ga-In-Sn for cooling, and the temperature is raised to 1600°C and then kept warm before directionally pulling. The directional solidification rate can be 2μm / s, the pulling distance can be 80mm, and the temperature gradient can be increased to 250K / cm.

[0032] In the present invention, the temperature of the solution treatment is 1260-1320° C., preferably 1280-1310° C. The temperature of the solution treatment affects the dissolution of the γ′ phase in the alloy. When the temperature is too low, the dissolution rate of the γ′ phase is low and the primary coarse γ′ phase cannot be eliminated; when the temperature is too high, the γ′ phase will completely dissolve. M6C carbides will precipitate during solution treatment. When carbides are granular and small in size, precipitate along the grain and grain boundary and are evenly distributed, they have a pinning effect, which can hinder dislocation movement and greatly improve the mechanical properties of the alloy. When the carbides are too large, the force transmission between the matrix is ​​cut off, the bonding force between the matrix is ​​weakened, and the carbide area is prone to stress concentration. At high temperatures, the thermal expansion coefficients between carbides and the matrix are different, and the interface between the two can produce large thermal stress. Therefore, carbides are easy to separate from the matrix during creep, becoming the initiation source of cracks, prompting the initiation and expansion of cracks between carbides / matrix, and becoming the weak link in the mechanical properties of the alloy. The temperature of the solution treatment is within the above range, which can make the γ′ phase dissolve well and will not precipitate large-sized secondary carbides.

[0033] In the present invention, the holding time of the solution treatment is 3 to 5 hours, preferably 3.5 to 4.5 hours. The holding time of the solution treatment affects the dissolution of the γ′ phase in the alloy. When the holding time is too short, the dissolution rate of the γ′ phase is low, and the primary coarse γ′ phase cannot be eliminated; as the holding time increases, the size of the M6C carbides precipitated at the grain boundaries will continue to increase, exceeding the optimal size range, and will waste processing time and energy. The holding time of the solution treatment is within the above range, which can make the γ′ phase dissolve better and control the size of the M6C carbide within a preferred range.

[0034] In the present invention, the cooling method of the solution treatment is preferably air cooling to room temperature. Compared with oil cooling and water cooling, air cooling is beneficial to improving the strength of the alloy.

[0035] In the present invention, the aging treatment is preferably performed once or twice.

[0036] In a technical solution of the present invention, the aging treatment is performed once, and the aging treatment is preferably low-temperature aging. The temperature of the low-temperature aging is preferably 800-900°C, more preferably 830-880°C, and further preferably 850-870°C; the holding time of the low-temperature aging is preferably 2-10h, more preferably 3-8h, and further preferably 4-6h. The temperature of the aging treatment affects the number and size of the secondary precipitation of the γ′ phase and the M 23 Precipitation of C6 carbides at grain boundaries: The temperature is too low, the γ′ phase precipitates too little and the size is too small, the carbides will not transform, and no granular M will precipitate. 23 C6 carbide; if the temperature is too high, the size of the γ′ phase is too large, and the evolution of the carbide will be relatively complicated. 23 C6 carbides have irregular morphology and may react to form harmful brittle phases; the holding time of aging treatment affects M 23 The morphology, size, and cubicity of the secondary precipitation of C6 carbide and γ′ phase increase with the increase of holding time. 23 The size of C6 carbide and γ′ phase gradually increases. When the holding time exceeds 4h, the volume fraction and cubic degree of γ′ phase gradually decrease. 23 Due to the influence of C6 carbide and γ′ phase, the low temperature aging temperature and holding time are within the above range, which is conducive to obtaining granular M 23 C6 carbides and appropriately sized, cubic γ′ phase.

[0037] In another technical solution of the present invention, the aging treatment is performed twice, and the aging treatment is preferably high-temperature aging and low-temperature aging performed sequentially; the temperature of the high-temperature aging is preferably higher than 900°C and not higher than 1000°C, and more preferably 930-970°C; the holding time of the high-temperature aging is preferably 2-4h; the temperature of the low-temperature aging is preferably 800-900°C, and more preferably 850-870°C; the holding time of the low-temperature aging is preferably 2-6h, and more preferably 3-5h. The present invention limits the parameters of the two aging treatments to the above range, which is conducive to obtaining granular, small-sized M 23 C6 carbides and appropriately sized, cubic γ′ phase.

[0038] In the present invention, the cooling method of the aging treatment is preferably air cooling to room temperature. Compared with oil cooling and water cooling, air cooling is beneficial to improving the strength of the alloy.

[0039] The present invention has no particular limitation on the heat treatment device, as long as it can meet the parameter requirements of the heat treatment. As an embodiment of the present invention, the heat treatment can be performed in an argon atmosphere.

[0040] The present invention dissolves the coarse primary γ′ phase through solid solution treatment to create conditions for the uniform precipitation of the secondary γ′ phase; controls the transformation of carbides at the grain boundaries during the solid solution treatment to uniformly precipitate M6C carbides at the grain boundaries; further regulates the secondary γ′ phase and carbides through aging treatment, controls the cubicity, size and volume fraction of the γ′ phase by controlling the temperature and time of the aging treatment, and makes the γ′ phase uniformly distributed with high density. The cubic γ′ phase has high interface stability, reduces interface energy and can uniformly disperse stress; at the same time, controls the precipitation of M6C carbides during the aging treatment. 23 C6 carbide makes it distributed in small, discrete points; the secondary γ′ phase and carbides precipitated after heat treatment have the effect of pinning dislocations, which can hinder dislocation movement, inhibit grain boundary sliding, and greatly improve the tensile properties and creep properties of nickel-based composites.

[0041] In an embodiment of the present invention, the heat treatment method of the directionally solidified high-carbon nickel-based composite material is as follows: Figure 1 As shown, the blank of the directionally solidified high carbon nickel-based composite material is solution treated at 1260-1320°C for 4h, and then subjected to one or two aging treatments. The one aging treatment is low-temperature aging at 870°C; the two aging treatments are high-temperature aging and low-temperature aging, the high-temperature aging temperature is 950°C, and the low-temperature aging temperature is 870°C.

[0042] The present invention also provides a high-carbon nickel-based composite material obtained by the heat treatment method described in the above technical solution, wherein the microstructure of the high-carbon nickel-based composite material includes a γ phase, a γ′ phase and carbides.

[0043] In the present invention, the microstructure of the high carbon nickel-based composite material includes a γ phase.

[0044] In the present invention, the microstructure of the high-carbon nickel-based composite material includes a γ′ phase, which is cubic. The cubic γ′ phase has high interface stability, reduces interface energy, can evenly disperse stress, and improves the tensile strength and yield strength of the alloy.

[0045] In the present invention, the size of the γ′ phase is 306-445 nm, and the volume fraction is 63.4-67.7%. As a reinforcing phase of the high-carbon nickel-based composite material, the size and volume fraction of the γ′ phase affect the tensile properties and creep properties of the material. The size and volume fraction of the γ′ phase within the above range are conducive to improving the tensile properties and creep properties of the material.

[0046] In the present invention, the microstructure of the high carbon nickel-based composite material includes carbides, and the carbides include MC, M6C and M 23 C6 carbide. In high-carbon nickel-based alloys, MC carbide is a major alloy reinforcement phase, which is continuous fiber-like in the alloy structure and effectively improves the tensile and creep properties of the alloy. During the heat treatment process, a small amount of MC carbide will undergo degradation reaction at the grain boundary, precipitating M6C and M 23 C6 carbide. M6C precipitates during solution treatment at a higher temperature. 23 C6 carbide has a relatively low precipitation temperature and precipitates during aging treatment. As a strengthening phase of high-carbon nickel-based composite materials, carbide has a pinning effect and a strengthening effect on grain boundaries, which can hinder dislocation movement, inhibit grain boundary sliding, and greatly improve the tensile and creep properties of the material.

[0047] In the present invention, the M6C carbide preferably has an area fraction of 0.5% to 1.5% and a size of less than 12 μm; 23 The size of C6 carbide is preferably less than 500nm. 23 C6 carbide is granular, much smaller in volume than MC carbide, precipitated along the grain boundary and evenly distributed, which can further improve the mechanical properties of the material; but when the carbide size is too large, it will cut off the force transmission between the matrix and weaken the bonding force between it and the matrix. The size of the carbide within the above range is conducive to improving the tensile properties of the material.

[0048] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0049] Comparative Example 1

[0050] The specific steps of casting of directional solidified high carbon nickel-based composite materials are as follows:

[0051] The composition of the material is 10.5% Co, 6.0% Al, 3% Nb, 8.5% Cr, 2.0% Mo, 7.5% W, 0.43% C, 0.5% V, and the rest is Ni. The high carbon nickel-based composite material is prepared by liquid metal cooling technology, the directional solidification rate is 2 μm / s, the pulling distance is 80 mm, the temperature is raised to 1600°C and then the temperature is kept, and the directional pulling is carried out, and Ga-In-Sn is used for cooling, and the temperature gradient is 250K / cm.

[0052] The morphology of the as-cast alloy was observed using a scanning electron microscope. Figure 2 As shown. Figure 2 (a) It can be seen that the carbide fibers (light-colored strips) are regularly and orderly arranged in the matrix; Figure 2 In (b), the dark area is the γ′ phase and the light area is the γ phase. It can be seen that the size of the γ′ phase in the as-cast structure of the directionally solidified high-carbon nickel-based composite material is at the micron level, coarse and irregular.

[0053] Example 1

[0054] The directionally solidified high-carbon nickel-based composite material prepared in Comparative Example 1 was placed in a quartz tube, argon was introduced, and the high-carbon nickel-based composite material was treated at 1300° C. for 4 hours, and air-cooled to room temperature to obtain a high-carbon nickel-based composite material after solution treatment. There was no initial melting phenomenon in the alloy during the solution treatment process.

[0055] The high carbon nickel-based composite material after the solution treatment is subjected to low temperature aging treatment at a temperature of 870°C for a holding time of 4 hours, and then air-cooled to room temperature to obtain a high carbon nickel-based composite material.

[0056] Example 2

[0057] The raw materials and preparation method are the same as those in Example 1, except that the solution treatment temperature is 1260°C.

[0058] Example 3

[0059] The raw materials and preparation method are the same as those in Example 1, except that the solution treatment temperature is 1280°C.

[0060] Example 4

[0061] The raw materials and preparation method are the same as those in Example 1, except that the solution treatment temperature is 1320°C.

[0062] The morphology of the high-carbon nickel-based composite materials after solution treatment in Examples 1 to 4 was observed using a scanning electron microscope. Figure 3 , Figure 4 As shown. Figure 3 It can be seen that when the solution temperature is 1260℃ and 1280℃, the primary γ′ phase is not completely dissolved (large dark areas), and when the solution temperature is 1300℃ and 1320℃, the primary γ′ phase is completely dissolved; and during the solution treatment, bright white secondary carbides precipitate along the grain boundaries. As the solution temperature increases, the precipitated secondary carbides gradually increase. Figure 4 It can be seen that the size of M6C carbides precipitated during the solution treatment of the alloy is about 12 μm.

[0063] Example 5

[0064] The raw materials and preparation method are the same as those in Example 1, except that the aging holding time is 2 h.

[0065] Example 6

[0066] The raw materials and preparation method are the same as those in Example 1, except that the aging insulation time is 6 hours.

[0067] Example 7

[0068] The raw materials and preparation method are the same as those in Example 1, except that the aging insulation time is 8 hours.

[0069] Example 8

[0070] The raw materials and preparation method are the same as those in Example 1, except that the aging insulation time is 10 h.

[0071] The morphology of the alloys after heat treatment in Examples 1, 5 to 8 was observed using a scanning electron microscope. Figure 5 , Figure 6 As shown. Figure 5 It can be seen that with the extension of the aging treatment holding time, the size of the γ′ phase gradually increases, the morphology of the γ′ phase gradually changes to a butterfly shape, the cubic degree becomes worse, and M 23 The C6 carbide does not change much with the extension of low temperature aging time. Figure 6 (a) It can be seen that the M precipitated during the aging process 23 C6 carbides are distributed along the grain boundaries in the form of discrete particles with a size less than 120nm; Figure 6(b) It can be seen that the MC carbide does not change much during the heat treatment process and still has a good fibrous structure, indicating that the MC carbide strengthening phase is not destroyed during the heat treatment process, and the M6C carbide and M 23 C6 carbide can further improve the tensile properties and creep properties of the alloy.

[0072] Example 9

[0073] The raw materials and preparation method are the same as those in Example 1, except that the aging treatment is performed twice, wherein the high-temperature aging temperature is 950°C, the holding time is 2 hours, and then low-temperature aging is performed after air cooling to room temperature, the temperature is 870°C, the holding time is 4 hours, and then air cooling to room temperature.

[0074] Example 10

[0075] The raw materials and preparation method are the same as those in Example 9, except that the high-temperature aging holding time is 4 hours.

[0076] The morphology of the alloys after treatment in Examples 9 to 10 was observed using a scanning electron microscope. Figure 7 As shown. Figure 7 It can be seen that when the high-temperature aging holding time is 2h, the size of the γ′ phase does not grow significantly compared with the solution treatment, the cubicity is poor, and it is round. When the high-temperature aging holding time is 4h, the size of the γ′ phase grows significantly and the cubicity is good; M 23 The C6 carbide increases slightly with the extension of high temperature aging time, but is still in granular form.

[0077] Comparative Example 2

[0078] The raw materials and preparation method are the same as those of Example 9, except that the high-temperature aging temperature is 1050°C.

[0079] Comparative Example 3

[0080] The raw materials and preparation method are the same as those of Example 10, except that the high-temperature aging temperature is 1050°C.

[0081] The morphology of the alloys after treatment in Comparative Examples 2 to 3 was observed using a scanning electron microscope. Figure 8 As shown. Figure 8 It can be seen that when the aging temperature is too high, the γ′ phase merges and becomes too coarse. 23 The size of C6 carbides increases significantly when aged at higher temperatures, and their morphology gradually becomes irregular.

[0082] Test Example 1: M6C carbide area fraction statistics

[0083] FEI-F50 field emission scanning electron microscope was used to select 5 to 10 observation fields on the lateral surface of the processed sample, with a magnification of 5000 times. ImageJ software was used to count the average area of ​​M6C carbides in each field, and the area fraction was calculated, as shown in Table 1.

[0084] Table 1 Statistics of average area of ​​M6C carbides

[0085] Alloy structure <![CDATA[Area fraction of M6C carbide]]> Example 1 0.89% Example 2 0.67% Example 3 0.82% Example 4 1.46%

[0086] from Figure 3 It can be seen from Table 1 that with the increase of solution treatment temperature, the area fraction of M6C carbides gradually increases.

[0087] Test Example 2: γ′ Phase Size Statistics

[0088] FEI-F50 field emission scanning electron microscope was used to select 5 to 10 observation fields on the transverse surface of the processed sample, with a magnification of 4000 times or 8000 times. ImageJ software was used to count the average area of ​​the γ′ phase in each field, and its equivalent size was calculated based on the average phase area of ​​the γ′ phase:

[0089] Square γ′ phase:

[0090] Spherical γ′ phase:

[0091] The statistical results of the γ′ phase size of each embodiment and comparative example are shown in Table 2.

[0092] Table 2 γ′ phase size statistics

[0093]

[0094]

[0095] It can be seen from Table 2 that, compared with the cast structure without heat treatment, the size of the γ′ phase of the alloy treated by the heat treatment method of the present invention is greatly reduced, and the sizes of the γ′ phase obtained by the two aging treatment methods are within the theoretical optimal size (300-500nm). When the aging treatment temperature is increased to 1050°C, the size of the γ′ phase increases to 636nm and 751nm.

[0096] Test case 3: γ′ phase volume fraction statistics

[0097] FEI-F50 field emission scanning electron microscope was used to select 5 to 10 observation fields on the transverse surface of the processed sample, with a magnification of 4000 times or 8000 times. ImageJ software was used to calculate the average area of ​​the γ′ phase in each field, and then the average size of the γ′ phase was calculated. The width of the γ channel was then calculated by measurement, and the sum of the γ′ phase and the γ channel A was obtained. The volume fraction f was calculated by the following formula: V .

[0098]

[0099] The statistical results of the volume fraction of the γ′ phase of each embodiment and comparative example are shown in Table 3.

[0100] Table 3 γ′ phase volume fraction statistics

[0101] Alloy structure Sum of γ′ phase and γ channel width (nm) γ′ phase volume fraction Comparative Example 1 1324 51.3% Example 1 Alloy after solution treatment 246 61.6% Example 1 348 67.7% Example 5 361 62.1% Example 6 423 57.6% Example 7 432 58.5% Example 8 437 61.7% Example 9 467 52.1% Example 10 518 63.4% Comparative Example 2 768 56.8% Comparative Example 3 853 68.3%

[0102] It can be seen from Table 3 that, compared with the cast structure without heat treatment, the volume fraction of the γ′ phase of the alloy treated by the heat treatment method of the present invention is significantly increased. The volume fractions of the γ′ phase obtained by the two aging treatment methods are both around the theoretical optimal volume fraction (65%), while the volume fraction of the γ′ phase is relatively low when the aging temperature is 1050°C.

[0103] Test Example 4: γ′ Phase Cubicity

[0104] By observation Figure 2 , Figure 5 and Figure 7 From the microstructure of the cast and heat-treated samples of the directionally solidified high-carbon nickel-based composite materials, it can be seen that the γ′ phase in the cast structure has an irregular morphology, coarse and uneven size; after appropriate heat treatment, the γ′ phase in the alloy structure has a high cubic degree and uniform size. After heat treatment regulation, the γ′ phase is closer to a cubic shape.

[0105] Test Example 5: 900℃ tensile test

[0106] The as-cast and heat-treated samples of the directionally solidified high-carbon nickel-based composite material were processed into "dog bone" tensile specimens. The as-cast and heat-treated samples were subjected to 900℃ high-temperature tensile tests (GB / T 228.2-2015) using a UTM5305 universal testing machine. The results are as follows Fig. 9 Each group of tensile tests was carried out at least twice, and the average values ​​of tensile strength and yield strength were measured and recorded in Table 4.

[0107] Table 4 Alloy tensile test performance test results

[0108] Alloy structure Comparative Example 1 Comparative Example 2 Example 1 Example 10 Tensile strength(MPa) 822.94 825.41 923.33 873.32 Yield strength(MPa) 700.91 726.33 856.96 788.69

[0109] from Fig. 9As can be seen from Table 4, compared with the cast sample, after heat treatment, the alloy showed obvious work hardening behavior, which may be related to the large proliferation of dislocations. Double yielding also occurred, which means that different mechanisms acted successively. After the two heat treatment processes were regulated, the tensile strength and yield strength of the alloy were greatly improved. The tensile strength of the sample treated with solid solution and once aging treatment increased by 12.2%, and the yield strength increased by 22.3%; the tensile strength of the sample treated with solid solution and twice aging treatment increased by 6.1%, and the yield strength increased by 12.5%.

[0110] Test Example 6: Creep Test

[0111] The as-cast sample of the directionally solidified high-carbon nickel-based composite material prepared in Comparative Example 1 and the alloy sample heat-treated in Example 1 were subjected to creep tests. When the creep temperature was 1000°C and the stress was 180MPa, the creep life of the as-cast alloy sample was 87.48h, and the creep life of the alloy after heat treatment in Example 1 was 222.97h. It can be seen that the creep life of the directionally solidified high-carbon nickel-based composite material was greatly improved after heat treatment.

[0112] It can be seen from the above embodiments and comparative examples that the heat treatment method provided by the present invention can obtain a γ′ strengthening phase with smaller size, uniformity and higher cubicity, resulting in a narrower γ channel. The high-density and evenly distributed γ′ phase makes it difficult for dislocations to bypass the γ′ phase during slip, and can effectively hinder the movement of dislocations by pinning them; after heat treatment, the cubicity of the γ′ phase is significantly improved, it has higher interface stability, reduces interface energy, can evenly disperse stress, and greatly improves the tensile strength and yield strength of the alloy; and the fine granular carbides precipitated along the grain boundaries after heat treatment can inhibit grain boundary slip, hinder the movement of dislocations, strengthen the grain boundaries, and are beneficial to improving the tensile properties and creep properties of the alloy.

[0113] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A heat treatment method for a directionally solidified high-carbon nickel-based composite material, comprising: The directionally solidified high-carbon nickel-based composite material is subjected to solution treatment and aging treatment in sequence; the temperature of the solution treatment is 1260-1320°C, and the insulation time is 3-5 hours; the temperature of the aging treatment is 800-1000°C, and the insulation time is 2-10 hours.

2. The heat treatment method according to claim 1, characterized in that The temperature of the solution treatment is 1280-1310° C., and the holding time is 3.5-4.5 hours.

3. The heat treatment method according to claim 1, characterized in that: The aging treatment is performed once or twice.

4. The heat treatment method according to claim 3, characterized in that: When the aging treatment is performed once, the aging treatment is low-temperature aging; the temperature of the low-temperature aging is 800 to 900° C., and the time is 2 to 10 hours.

5. The heat treatment method according to claim 3, characterized in that: When the aging treatment is performed twice, the aging treatment is high temperature aging and low temperature aging performed sequentially.

6. The heat treatment method according to claim 5, characterized in that: The temperature of the high-temperature aging is higher than 900° C. and not higher than 1000° C., and the time is 2 to 4 hours; the temperature of the low-temperature aging is 800 to 900° C., and the time is 2 to 6 hours.

7. The heat treatment method according to any one of claims 1 to 6, characterized in that: The components of the directionally solidified high-carbon nickel-based composite material are as follows by mass percentage: 9.5-11.0% Co, 5.5-6.5% Al, 3.0-3.5% Nb, 8.0-9.0% Cr, 1.6-2.5% Mo, 7.2-7.9% W, 0.4-0.46% C, 0.4-0.55% V, and the balance Ni.

8. The heat treatment method according to claim 1, characterized in that: The directionally solidified high-carbon nickel-based composite material is prepared by liquid metal cooling technology.

9. The high-carbon nickel-based composite material obtained by the heat treatment method according to any one of claims 1 to 8, characterized in that: The microstructure of the high-carbon nickel-based composite material includes a γ phase, a γ′ phase and carbides; the γ′ phase is cubic, the size of the γ′ phase is 306-445 nm, and the volume fraction of the γ′ phase is 63.4-67.7%; the carbides include MC, M6C and M 23 C6 carbide.

10. The high carbon nickel-based composite material according to claim 9, characterized in that: The MC carbide is fibrous; the size of the M6C carbide is less than 12 μm, and the volume fraction is not higher than 1.5%; 23 The size of C6 carbides is less than 500 nm.